Pengaruh Durasi Penggunaan Media Sosial terhadap Konsentrasi Belajar - Hafizhotul Mumtazah; Ellen Prima (INDO PUBLISHING, 2026)
The academic focus of students today is increasingly vulnerable to being disrupted by the high intensity of social media usage, despite the communication conveniences the platform offers. This phenomenon prompts this study, which aims to analyze how the duration of social media use affects students' learning concentration. Employing a quantitative method with a correlational design, this research involved a randomly selected sample of students who completed a questionnaire, with the data subsequently processed through simple linear regression analysis. The results confirm a significant negative correlation: the longer students browse social media daily, the more their learning concentration declines during the instructional process. Recommendations from this study emphasize the critical importance of collaboration between schools and parents to limit device screen time and teach prudent time management to students.